1996
DOI: 10.1063/1.472473
|View full text |Cite
|
Sign up to set email alerts
|

Polarization effects in time resolved incoherent anti-Stokes Raman spectroscopy

Abstract: Coherent antiStokes Raman spectroscopy of shockcompressed liquid nitrogen/carbon monoxide mixturesRecently the anti-Stokes spectroscopy after strong vibrational excitation via resonant absorption was rediscovered, for the study of population relaxation dynamics. A closer theoretical inspection of this experimental approach reveals that properly chosen polarization conditions allow the study of molecular reorientational motion. Furthermore the sign of a/␥ ͑the invariants of the Raman polarizability tensor͒ can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Vibrational relaxation data are normally described in terms of rate equations, which include the orientational motion via angle dependencies . It will turn out that the reorientation of chloroform is much faster than the vibrational relaxation; therefore, it can be neglected for the following discussion of the long-time evolution vibrational relaxation. Upon an excess population Δ n i 0 being produced at t = 0, the time dependence of the excess population of the i th vibrational state Δ n i (t) is described by …”
Section: Interpretation and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vibrational relaxation data are normally described in terms of rate equations, which include the orientational motion via angle dependencies . It will turn out that the reorientation of chloroform is much faster than the vibrational relaxation; therefore, it can be neglected for the following discussion of the long-time evolution vibrational relaxation. Upon an excess population Δ n i 0 being produced at t = 0, the time dependence of the excess population of the i th vibrational state Δ n i (t) is described by …”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…Therefore, only limited information about the relaxation pathways was available. Recently the anti-Stokes spectroscopy after strong vibrational excitation via resonant absorption was rediscovered. By the help of high-sensitive multichannel detection setups, the time evolution of complete anti-Stokes spectra can be observed and analyzed. In the following section, a rather complete data set will be presented: after excitation of the CH stretching vibration of chloroform, time dependent changes of the anti-Stokes Raman scattering of all fundamental vibrational transitions were simultaneously observed.…”
Section: Introductionmentioning
confidence: 99%
“…Hofmann et al have experimentally shown that time-dependent Raman signals can decrease by more than B50% due to rotational diffusion. 60 For a molecule the size of NBA dissolved in acetonitrile rotational diffusion times in the range of the measured bleach recovery (B10 ps) are to be expected. 61 So vibrational cooling and rotational diffusion might contribute to the B10 ps bleach recovery.…”
Section: Fsrs Experimentsmentioning
confidence: 96%
“…The same authors also studied intermolecular vibrational energy transfer between alcohols and nitromethane. 24 Recently, Graener and co-workers used a 50 Hz Nd : YLF system with 1.5 ps resolution to study VER in dichloromethane 25 (CH 2 Cl 2 ) and chloroform 26 (CHCl 3 ) after C-H stretch excitation. The latter work 26 is especially notable for being the first where every one of the vibrations of a particular polyatomic molecule was monitored during a VER process.…”
Section: Introductionmentioning
confidence: 99%